The study of packaging miniaturization effect on the characteristics of an active planar circuit by using the iterative method. (13th August 2012) - Ziar, Toufik; Zaabat, Mourad; Baudrand, Henri
SUMMARY: The aim of this manuscript is to present the application of an iterative method based on the concept of transverse wave to analyze the packaging (passive element and substrate) miniaturization effect on the characteristics of an active planar circuit structure. This approach consists in the substitution of the active element by one auxiliary source, and connection is assumed by microstrip line as passive element deposited on one unique substrate. An implementation of the presented theory is shown by extraction of S ‐parameters and impedances of the active circuit using MATLAB program codes. Copyright © 2012 John Wiley & Sons, Ltd.